2012
DOI: 10.1016/j.intimp.2012.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Role of interplay between IL-4 and IFN-γ in the in regulating M1 macrophage polarization induced by Nattectin

Abstract: Recently our group described that Nattectin, a C-type lectin of the venom of Thalassophryne nattereri shows a potent pro-inflammatory capacity. Here, we demonstrated that Nattectin is able to induce M1 macrophage marker iNOS, and up-regulate the expression of MHC class II, CD80, CD86 and CD40 molecules. The increase in MHC class II and CD49a integrin expression with MMP-9 production and endocytic capacity depend on lectin function of Nattectin. Moreover, the polarization of peritoneal and bone marrow-derived m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 48 publications
1
29
0
Order By: Relevance
“…These data show that CRA exposure has a significant effect on the lung macrophage population, as assessed by their surface expression levels of CD80 and CD86. Studies by other groups using these molecules as M1 markers (19,35,39) suggest that our observations represent genuine phenotypic changes. This provides evidence suggesting a role for macrophage phenotypes in the pathogenesis seen in our model.…”
Section: E and F)mentioning
confidence: 51%
See 3 more Smart Citations
“…These data show that CRA exposure has a significant effect on the lung macrophage population, as assessed by their surface expression levels of CD80 and CD86. Studies by other groups using these molecules as M1 markers (19,35,39) suggest that our observations represent genuine phenotypic changes. This provides evidence suggesting a role for macrophage phenotypes in the pathogenesis seen in our model.…”
Section: E and F)mentioning
confidence: 51%
“…In this study, we have shown that exposure to CRA has a significant effect on macrophage phenotypes, increasing the number of macrophages in the lung and reducing their surface expression of CD80 and CD86, molecules, which, among others, have been previously established as useful in assessing the phenotype of macrophages (1,10,19,20,35,39,51). We have also developed a novel procedure to supplement the lung macrophage population in our outbred mouse model; to our knowledge the use of an ATM has never been investigated in the CRA-induced asthma model.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…& Fatima Laraba-Djebari flaraba@hotmail.com; flaraba@usthb.dz fish venom, was able to induce macrophage activation and upregulate the expression of NOS 2 [10]. In addition, the toxic components from Tityus serrulatus (TSV) venom stimulated the release of NO in the presence of LPS in the murine macrophage cell line [11].…”
Section: Introductionmentioning
confidence: 99%